2015
DOI: 10.1155/2015/493191
|View full text |Cite
|
Sign up to set email alerts
|

The Calcium Sensor CBL-CIPK Is Involved in Plant’s Response to Abiotic Stresses

Abstract: Abiotic stress halts the physiological and developmental process of plant. During stress condition, CBL-CIPK complex is identified as a primary element of calcium sensor to perceive environmental signals. Recent studies established that this complex regulates downstream targets like ion channels and transporters in adverse stages conditions. Crosstalks between the CBL-CIPK complex and different abiotic stresses can extend our research area, which can improve and increase the production of genetically modified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
41
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 100 publications
(141 reference statements)
3
41
0
Order By: Relevance
“…This protein forms a calcium‐sensing complex with CBL1 or CBL9 (CALCINEURIN B‐LIKE PROTEIN), which is involved in iron, nitrate and potassium transport and sensing (Léran et al . ; Manik et al ; Tian et al ). Its role in regulating nitrate transport and signalling by the NITRATE TRANSPORTER 1.1 (NRT1.1) transceptor (duel nutrient transport/signalling function) and the crucial role this plays in the regulation of ABA levels in seeds is well characterized (reviewed in Finch‐Savage and Footitt ).…”
Section: Discussionmentioning
confidence: 99%
“…This protein forms a calcium‐sensing complex with CBL1 or CBL9 (CALCINEURIN B‐LIKE PROTEIN), which is involved in iron, nitrate and potassium transport and sensing (Léran et al . ; Manik et al ; Tian et al ). Its role in regulating nitrate transport and signalling by the NITRATE TRANSPORTER 1.1 (NRT1.1) transceptor (duel nutrient transport/signalling function) and the crucial role this plays in the regulation of ABA levels in seeds is well characterized (reviewed in Finch‐Savage and Footitt ).…”
Section: Discussionmentioning
confidence: 99%
“…It has been found that CBL-CIPK pathways work as regulators in nutrients transport systems, regulating sodium (Na + ) [180], potassium(K + ) [182], magnesium (Mg 2+ ) [183], nitrate (NO 3 − ) [184], and proton (H + ) homeostasis [185]. Recently, in some reviews, particular attention to the possible involvement of the CBLs and CIPKs in different ions sensitivity has been drawn [186,187]. As calcium sensor relieves in plants, calcineurin B-like (CBL) proteins provide an important contribution to decoding Ca 2+ signatures elicited by a variety of abiotic stresses.…”
Section: Physiological Roles Of Cbls and Cipks In Plant Responses To mentioning
confidence: 99%
“…The AtCBL-AtCIPK complex has been heavily implicated in abiotic stress tolerance by adjusting the levels of K + through AtAKT1 (Manik et al, 2015). Of the 26 different CIPKs identified within the Arabidopsis genome, AtCIPK10, AtCIPK11, AtCIPK12, AtCIPK14, and AtCIPK19 are strongly expressed in PTs (Konrad et al, 2011;Zhou et al, 2015a).…”
mentioning
confidence: 99%